Analysis of hygrothermal variationbetween rural and urban areas critically low humidity period in Vale do Rio Cuiabá - Valin Junior, Marcos de Oliveira; Ribeiro, Karyn Ferreira Antunes; Santos, Flávia Maria de Moura; Nogueira, Marta Cristina de Jesus Albulquerque; Musis, Carlo Ralph de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This paper aims to analyze and compare the data of temperature and humidity of two geographically close municipalities, but with different hygrothermal behavior. The two municipalities were chosen Santo Antonio do Leverger (Rural) and Cuiabá (Urban). Data were collected from two micrometeorological stations located in their locality. The proposed period for the study were the months of June, July and August 2014, corresponding to hot-dry season. The tools that assisted in the analysis of the data statistically and graphically were the SPSS version 22.0 and Excel software. The results show a difference of nearly 2 ° C average temperature of county air in the "Rural" about the "Urban", and humidity the difference reached 25%. With these data, we can see how the use and occupation soil can interfere with hygrothermal characteristics from one region to another.